U-Prove Designated-Verifier Accumulator Revocation Extension - Paquin, Christian; Nguyen, Lan (Microsoft Research, 2015)
This document extends the U-Prove Cryptographic Specification by specifying an efficient revocation mechanism based on a dynamic accumulator. This scheme requires a designated verifier that shares the Revocation Authority’s private key. Unlike many accumulator schemes based on bilinear pairings, this scheme is built using a prime-order group and is therefore suitable for system that require standard constructions used in the U-Prove protocol.